4 kV class splicing device to connect high-voltage instrumentation wires and cable. (July 2019) - Cao, Yi; Pan, Wanjiang; Laurenti, Adamo; Journeaux, Jean-Yves; Wu, Cheng; Zhu, Yinfeng
Highlights: The 4 kV SD without HV shield is cryogenic temperature resistant. The 4 kV SD without HV shield is helium tightness, which can avoid Paschen discharge. The signal fault location can be tracked conveniently by using SD. Abstract: In ITER machine, the splicing devices (SDs) are designed to connect the high voltage (HV) individual wires bringing the signal from the sensors installed in the superconducting magnet system to the HV cables connected with the feedthroughs installed in the cryostat wall. SDs shall be designed and manufactured to ensure its safety operation at 4.5 K and under the environment of ionizing radiation and high magnetic field. As a kind of insulating structural part, the structural design of prototype SD aimed at achieving enough safe margin of insulating performance under helium (He) gas condition. To evaluate the electrical properties, a prototype SD was fabricated and the HV-leakage current tests were performed, the testing results indicate that the leakage currents are less than 2 μA under 4 kV DC and 20 μA under 4 kV AC respectively, which are less than the allowable values 5 μA and 30 μA. In addition, the testing results also indicate that there was no breakdown or current impulse occurred during Paschen discharge tests. However, when the bonded interface is not He gas tightness, SD can be damaged by Paschen discharge.